Associated Press news dispatches - Associated Press. Washington Bureau
Collection of news dispatches from the Washington D.C. Bureau of the Associated Press spanning 15 years and containing an unbroken chronology of world and national events as reported by the news agency.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: History, Modern -- 20th century; News agencies; News dispatches; United States -- History -- 20th century